2020
DOI: 10.12928/eltej.v3i2.2349
|View full text |Cite
|
Sign up to set email alerts
|

Exploring EFL Students’ Perception of Online Learning via Microsoft Teams: University Level in Indonesia

Abstract: An internet connection has been crucial in the era of globalization to enhance human activities in various activities of economic, culture, defense, and many others, especially in the EFL classroom setting. Microsoft Teams as an innovative online learning platform provides unique features to enhance its potential to help EFL teachers to conduct better interaction as well learning environment in online learning. This research aimed at exploring students’ perceptions of online learning via Microsoft Teams. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 14 publications
5
99
0
10
Order By: Relevance
“…Since students are one of the most crucial stakeholders of higher education (Ömer et al, 2015), students' perceptions toward online learning are closely related to the success of online learning (Agung, Surtikanti & Quinones, 2020). Accordingly, much research (e.g., Rojabi, 2020;You, 2019;Zaveri et al, 2020) has been conducted to investigate students' perceptions toward online learning. As technical accessibility/stability has been one of the most critical challenges in the online learning environment (e.g., Agung et al, 2020), many universities have been equipped with online resources and technologically supportive for their students and instructors.…”
Section: Covid-19 and Online Learningmentioning
confidence: 99%
“…Since students are one of the most crucial stakeholders of higher education (Ömer et al, 2015), students' perceptions toward online learning are closely related to the success of online learning (Agung, Surtikanti & Quinones, 2020). Accordingly, much research (e.g., Rojabi, 2020;You, 2019;Zaveri et al, 2020) has been conducted to investigate students' perceptions toward online learning. As technical accessibility/stability has been one of the most critical challenges in the online learning environment (e.g., Agung et al, 2020), many universities have been equipped with online resources and technologically supportive for their students and instructors.…”
Section: Covid-19 and Online Learningmentioning
confidence: 99%
“…Previous studies (e.g., [39][40][41]) have been conducted to study students' perceptions of using MS Teams application in online learning. A recent study [39] showed that during the COVID-19 pandemic, students had a positive impression of MS Teams usage in online learning.…”
Section: Microsoft Teams As An E-learning Platform For Higher Education Institutionsmentioning
confidence: 99%
“…A study [42] also reported other disadvantages for using MS Teams as an online learning platform such as lack of interaction between students themselves and their educators as well, which leads to social isolation; lack of communication that usually leads to mental issue such as negative thoughts; and lack of self-motivation with bad time management. Additionally, there are some problems faced by MS Teams users such as insufficient internet facilities, invisible image display, and unclear voice [41]. To that end, the use of MS Teams as an online learning tool is still in its infancy, especially in higher education.…”
Section: Microsoft Teams As An E-learning Platform For Higher Education Institutionsmentioning
confidence: 99%
“…Kung pagtutuunan ng pansin ang nilalaman ng mga kaugnay na pag-aaral, matutuklasan na marami ang tumatalakay sa persepsyon at danas ng mga mag-aaral sa online learning. Umiikot ang mga ito sa iba't ibang pokus at dimensyon: sa panahon ng COVID-19 (Khan, Vivek, Nabi, Khojah, & Tahir, 2020); sa kagamitang panturo (Armstrong, 2011); estratehiyang panturo sa online classroom (Lowenthal & Dunlap, 2018); gamit ng isang partikular na online platform (Rojabi, 2020); tungkol sa pagtuturo ng guro (Tucker, Halloran, & Price, 2013); at pangkalahatang pagsusuri sa persepsyon ng mga mag-aaral (Nwankwo, 2015;Fidalgo, Thormann, Kulyk, & Lencastre, 2020;Kulal & Nayak, 2020;Yee, 2011;Huss & Shannon, 2013). Lubha itong marami kung ikukumpara sa mga pag-aaral na tumatalakay naman sa persepsyon ng mga mag-aaral sa face-to-face at online learning (Mather & Sarkans, 2018;La Piana, 2014;Bali & Liu, 2018;Otter, Seipel, Graeff, Boraiko, Gray, Petersen, & Sadler, 2013;Kemp & Grieve, 2014).…”
Section: Pagtalakayunclassified